Pengaruh Komitmen Organisasi, Gaya Kepemimpinan, dan Ketidakpastian Lingkungan terhadap Hubungan Partisipasi Anggaran dengan Kinerja Manajerial - Cahyadi, Riandy Sugiharto; Handoko, Jessica (Widya Mandala Surabaya Catholic University, 2010)
This study wanted to examine the influence of organizational commitment, leadership style and the uncertainty of the environment on the relationship between budget participation with managerial performance. The research objective was to determine the impact of (1) the budget participation with managerial performance; (2) organizational commitment to the relationship between budget participation with managerial performance; (3) leadership style on the relationship between budget participation with managerial performance and (4) environmental uncertainty on the relationship between the budget participation with performance managerial. The study respondents were middle level managers. Data collected is processed by regression analysis interactions between variables. The research results are (1) there is a positive impact of the budget participation on managerial performance, (2) the influence of the interaction between organizational commitment with budget participation on managerial performance, (3) the absence of interaction effects between leadership styles with budget participation on managerial performance, and; (4) the influence of the interaction between environmental uncertainty with budget participation on managerial performance.